Average intensity and coherence properties of a partially coherent Lorentz-Gauss beam propagating through oceanic turbulence. (1st January 2018) - Liu, Dajun; Wang, Guiqiu; Wang, Yaochuan
Highlights: Equations of partially coherent Lorentz-Gauss beam in oceanic turbulence are obtained. The spreading properties of beam in oceanic turbulence is illustrated. The influences of beam parameters on the propagation properties is studied. The influences of oceanic turbulence on the average intensity is obtained. Abstract: Based on the Huygens-Fresnel integral and the relationship of Lorentz distribution and Hermite-Gauss function, the average intensity and coherence properties of a partially coherent Lorentz-Gauss beam propagating through oceanic turbulence have been investigated by using numerical examples. The influences of beam parameters and oceanic turbulence on the propagation properties are also discussed in details. It is shown that the partially coherent Lorentz-Gauss beam with smaller coherence length will spread faster in oceanic turbulence, and the stronger oceanic turbulence will accelerate the spreading of partially coherent Lorentz-Gauss beam in oceanic turbulence.